“One thousand days of degradation”: new Labour and old compromises at the turn of the century - Joe (Social justice, 2000)
Part of a special issue on criminal justice at the new millennium. The writer explores the law-and-order strategy of New Labour (NL), the ruling party in Britain. He outlines this strategy in the context of 20 years of near-Conservative hegemony and the influence of that hegemony on NL's conceptualization of crime and punishment. He examines events in the first months of 2000, ranging from the refusal to extradite the former Chilean dictator Augusto Pinochet, to the sentencing of an armed robber to 22 life sentences for his crimes. He also analyzes NL's dedication to human rights through the European Convention on Human Rights. He concludes that NL's narrow, legalistic view of human rights could result in the marginalization of material social processes that are vital to the delivery of democratic accountability and social justice in British society.